The Pathologist's Story and the Colors - Francisco Javier Torres Gómez (Journal of Clinical and Diagnostic Pathology, 2021)
This essay reflects on the craft of diagnostic pathology, using color and pattern as a narrative lens. Through case vignettes, it illustrates how morphology, staining, and visual reasoning translate into clinical answers. The perspective emphasizes communication, uncertainty management, and the human dimension of laboratory work.
Keywords: Diagnostic Pathology